1992
DOI: 10.1111/tri.1992.5.s1.613
|View full text |Cite
|
Sign up to set email alerts
|

Detection of latent human cytomegalovirus in organ tissue and the correlation with serological status

Abstract: The presence of human cytomegalovirus (HCMV) genome in spleen tissue was studied by using DNA hybridization techniques in seropositive and seronegative organ donors without clinical or laboratory confirmed HCMV infection. The serum samples of these patients were screened by latex agglutination test (LA) and enzyme linked immuno sorbent assay (ELISA) for the presence of HCMV antibodies, and confirmed by immunoblotting technique (IB ). For the detection of HCMV sequences in spleen tissue dot blot DNA hybridizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Many men who were CMV seronegative still had CMV infected prostates. This is not surprising, as it is well established that CMV serostatus substantially underestimates the proportion of individuals who are infected by CMV [15][16][17][18][19][20][21][22] . Thus, we are not exclusively comparing groups of individuals who are CMV infected or not, but who are infected to varying degrees.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Many men who were CMV seronegative still had CMV infected prostates. This is not surprising, as it is well established that CMV serostatus substantially underestimates the proportion of individuals who are infected by CMV [15][16][17][18][19][20][21][22] . Thus, we are not exclusively comparing groups of individuals who are CMV infected or not, but who are infected to varying degrees.…”
Section: Discussionmentioning
confidence: 87%
“…In CMV seropositive post-mortem donors (24/41, 59%), the proportion of the prostate epithelial cells that was infected by CMV ranged from 2% to 100% with a mean of 58%, as assessed by the detection of the CMV protein pp71 by IHC (n=24, Figure 1A). It is well established that CMV infected individuals often are seronegative [15][16][17][18][19][20][21][22][23][24][25][26] , and prostates from the 17 CMV seronegative post-mortem donors were all CMV IHC positive, but epithelial abundance of CMV was significantly lower than in CMV seropositive post-mortem donors with a mean of 28% (p<0.0001, Figure 1A).…”
Section: Relationship Between CMV Serostatus and Cmv Infection In The...mentioning
confidence: 97%
See 1 more Smart Citation
“…Although several previous studies found that reinfection with donor-derived strains are more common than reactivation of recipient virus (Grundy et al, 1988)(Chou, 1986)(Sunwen & Norman, 1988), others have argued that infections post-transplantation are approximately equally donor- and recipient-derived (Manuel, Pang, et al, 2009). Reports on the detection of HCMV in tissues of non-immunocompromised individuals (Schonian et al, 1993)(Kytö et al, 2005)(Kraat et al, 1992)(Hendrix et al, 1997)(Meyer-König et al, 1998) further underline the potential of HCMV transmission with the allograft, yet the extent of transmission remained controversial. In the present study, we could demonstrate HCMV-DNA positivity in 5/10 pre-transplant lungs of HCMV-seropositive donors, with up to three HCMV genotypes present in small HCMV-DNA positive tissue sections of a single donor lung.…”
Section: Discussionmentioning
confidence: 99%
“…Human cytomegalovirus (CMV) is a herpes virus, which the majority of humans are chronically infected by, indicated by 83% having antibodies against the virus 6 . This is likely a substantial underestimation of the proportion of the population that is infected, as it is very common to detect CMV DNA in seronegative individuals [7][8][9][10][11][12][13][14] , indicating that they are infected but lack a detectable antibody response. CMV seropositivity is associated with increased general cancer mortality in men 15 , but not associated with prostate cancer incidence 16,17 .…”
Section: Introductionmentioning
confidence: 99%